DELTAIC AND SHELF DEPOSITIONAL PACKAGES OF THE GULANI MEMBER OF PINDIGA FORMATION, GONGOLA SUB-BASIN, NORTHERN BENUE TROUGH, N.E. NIGERIA - Shettima, B.; Goro, A.I.; Bukar, M.; Mohammed, Y.B. (International Journal of Research -GRANTHAALAYAH, 2018)
Stratigraphic and facies analysis of the Gulani Member of the Pindiga Formation in the Gongola Sub-basin of the Northern Benue Trough indicated that the lithostratigraphic architecture of the formation are characterized by three bioturbated lithologic units. These includes the lower succession of heterolithic units with fine grained sandstones and mudstone interbeds, passing into succession of medium-coarse grained sandstone with dominantly trough crossbeds and a upper succession of medium grained trough crossbedded sandstone and mudstone interbeds. Facies evaluation of these distinct succession indicated development of a corresponding pro-delta sands and clays, moving into delta front sands and then shelf sandstone and claystone respectively. Thus suggesting that the Gulani Member was generally formed in a coastal setting defined by river dominated deltaic setting and shelf depositional environment.